1999
DOI: 10.1086/303208
|View full text |Cite
|
Sign up to set email alerts
|

Specific Hypotheses on the Geographic Mosaic of Coevolution

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. abstract: Coevolution is one of the major processes organizing the earth's biodiversity. The need to understand coevolution as an ongoing process has grown as ecological conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
854
4
20

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 749 publications
(915 citation statements)
references
References 80 publications
37
854
4
20
Order By: Relevance
“…In contrast, other phylogeographic breaks shared by Heligmosomoides and A. sylvaticus in South Western Europe do not correspond to phylogeographic breaks typically found in many other taxa: i.e., the differentiation of Sicily from continental Italy (even if few studies showed that Sicily is a hotspot of biodiversity in Europe (Randi et al, 2003;Fineschi et al, 2005;Fritz et al, 2005)), and the differentiation of Maghreb populations from Spain. These shared specific phylogeographic breaks are, in contrast to usual phylogeographic fractures, good clues arguing for long-term co-differentiation between the two species (Thompson, 2005). Third, this study confirmed that co-differentiation was significantly more likely than independent history between A. sylvaticus and Heligmosomoides in south Western Europe (TREEMAP analyses, Fig.…”
Section: Regional Co-differentiation Between Heligmosomoides and A Ssupporting
confidence: 75%
“…In contrast, other phylogeographic breaks shared by Heligmosomoides and A. sylvaticus in South Western Europe do not correspond to phylogeographic breaks typically found in many other taxa: i.e., the differentiation of Sicily from continental Italy (even if few studies showed that Sicily is a hotspot of biodiversity in Europe (Randi et al, 2003;Fineschi et al, 2005;Fritz et al, 2005)), and the differentiation of Maghreb populations from Spain. These shared specific phylogeographic breaks are, in contrast to usual phylogeographic fractures, good clues arguing for long-term co-differentiation between the two species (Thompson, 2005). Third, this study confirmed that co-differentiation was significantly more likely than independent history between A. sylvaticus and Heligmosomoides in south Western Europe (TREEMAP analyses, Fig.…”
Section: Regional Co-differentiation Between Heligmosomoides and A Ssupporting
confidence: 75%
“…Another set of potential reasons for varied results in local hostparasite adaptation studies is untested interactions with other factors related to evolutionary history or ecological context (Thompson, 1994(Thompson, , 1999Morgan et al, 2005). Evolutionarily, different host lineages and their co-evolved parasites could have had different histories of selection, genetic bottlenecks, drift and founder events which might have strongly shaped co-evolutionary trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…In four species of damselflies parasitized by a generalist ectoparasite, Yourth et al (2001) concluded that temporal and spatial variation in abundance did not fully explain interspecific variation in immune response. However, immune response T A geographic range increases, the more parasite species it should encounter, which leads to that host species evolving stronger generalised immune responses (Thompson 2005). This could lead to observations where the more widespread and locally abundant host species are less parasitized.…”
Section: Introductionmentioning
confidence: 99%